The Influence of Digital Leadership, Digital Innovation and Organizational Learning on Digital Maturity to Improve Organizational Performance: Empirical Study from PT. Perkebunan Nusantara IV Regional III, Indonesia - Heriansyah, T.; Zulfadil, Z.; Maulida, Yusni (Manunggal Halim Jaya, 2025)
The study was conducted at PT. Perkebunan Nusantara IV Regional III. The aim was to determine the direct influence of digital leadership, digital innovation, and organizational learning on digital maturity to improve organizational performance. The study took a sample of 207 employees. The variables used were digital leadership, digital innovation and organizational learning, digital maturity, and organizational performance. The data were analyzed using SEM (Structural Equation Modeling) analysis operated through the Smart PLS 4.0 program. The results of the study indicate that digital leadership, digital innovation, and organizational learning have a significant influence on digital maturity. Digital maturity itself has been proven to have a significant influence on improving organizational performance. In addition, the influence of digital leadership, digital innovation, and organizational learning on organizational performance is also strengthened through the mediation of digital maturity. Thus, digital maturity plays an important role as a liaison that optimizes the impact of independent variables on organizational performance.